Idiopathic segmental anhidrosis and harlequin syndrome - Nakazato, Yoshihiko (The Autonomic Nervous System, 2019)
Harlequin syndrome and segmental anhidrosis represent segmental dyshidrosis. Harlequin syndrome is defined as paroxysmal hemifacial flushing and hyperhidrosis, and many cases accompany contralateral segment anhidrosis. This syndrome is considered as idiopathic segmental anhidrosis with compensatory hyperhidrosis in the contralateral side. Harlequin syndrome is divided into secondary and idiopathic types by its etiology. Lung cancer (pancoast tumor), neurinoma and carotid artery dissection are main causes of secondary harlequin syndrome. It is classified into three groups by anatomical focus as follows: 1) hypothalamus to spinal cord, 2) apex area and superior mediastinum, 3) cervical part or internal carotid artery area. Idiopathic segmental anhidrosiss is often associated with Adie’s syndrome (Adie’s pupil plus absence of tendon reflex), and this state is called Ross syndrome. Sjögren syndrome and herpes zoster virus infection are considered as causative diseases of Ross syndrome and/or idiopathic segmental anhidrosis. It is considered that the pathogenesis of Ross syndrome is an immunological mechanism for target antigens of the sympathetic ganglion, the ciliary ganglion, and the dorsal root ganglion.